Direct Nerve Sutures in (Extended) Upper Obstetric Brachial Plexus Repair - Bahm, J.; Gkotsi, A.; Bouslama, S.; El-kazzi, W.; Schuind, F. (Journal of Brachial Plexus and Peripheral Nerve Injury, 2017)
Background In rare, selected cases of severe (extended) upper obstetric brachial plexus palsy (OBPP), after supraclavicular exposure and distal mobilization of the traumatized trunks and careful neuroma excision, we decided to perform direct nerve coaptation with tolerable tension and immobilized the affected arm positioned in adduction and 90-degree elbow flexion for three weeks.Objectives We present our surgical technique and preliminary results in a prospective open patient series, including 22 patients (14 right and 8 left side affected) between 2009 and 2016, operated at a mean age of 8.4 months.Methods Analysis of functional results after a minimum of 18 months was conducted using the British Medical Research Council (BMRC) scale.Results All children reached 60–90° of elbow flexion and 75° of shoulder abduction at already six months after surgery. For those patients having already passed one year post surgery, the mean active shoulder abduction reached 92°, and for those who past the 18 months 124°. We discuss the actual knowledge about nerve coaptation under “reasonable” tension including its advantages and drawbacks.Conclusion This technique may be indicated in preoperatively selected cases of (extended) upper OBPP and may give good functional results.
Keywords: brachial plexus injury; obstetric brachial plexus palsy; microsurgery; nerve repair; direct suture; tension